Identification of proteomic markers for metastasis of ovarian cancer - V. E. Shevchenko; D. E. Makarov; S. V. Kovalev; N. E. Arnotskaya; N. R. Pogosyan; K. I. Zhordania (ABV-press, 2014)
The proteome of ascites and pleural fluids (AF and PF) was mapped in patients with ovarian cancer (OC). 240 and 190 proteins were identi- fied with a high degree of assurance in A F and PF, respectively . The major portion w as extracellular and membrane proteins, whi ch ac- counted for 45 and 49 % in AF and PF, respectively. Analysis of the proteomic maps of AF and PF indicated that 82 proteins were common to these biological fluids whereas 81 and 49 proteins were unique to A F and PF, respectively. A list of 46 potential markers for O C metastasis and potential markers for tropic OC metastasis over the peritoneal (17 proteins) and pleural (11 proteins) surfaces is given.